Sbornyĭ listʺ kartʺ i planovʺ Si︠e︡vernago Ledovitago okeanʺ i Bi︠e︡lago mori︠a︡ sostavlena vʺ 1908 g. / Izdanīe Glavnago Gidrograf. Upravl. Mgo Mstva vʺ 1909 g. - Russia. Glavnoe gidrograficheskoe upravlenīe; ([Санкт-Петербург] : Морское министерство, Главное гидрографическое управленіе; Sankt-Peterburg : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe;, 1909)
Title translation: Collection sheet of maps and plans of the Arctic Ocean and the White Sea compiled in 1908.; Maps: Si︠e︡vern. beregʺ Rossīi otʺ Norevegīi do Beringova proliva -- Novai︠a︡ Zemli︠a︡ Timanskīĭ i Bolʹshezemelʹskīĭ beregʺ -- Bi︠e︡loe more -- Murmanskīĭ beregʺ.; Maps titles translations: Northern coast of Russia from Norway to the Bering Strait. -- Novaya Zemlya, Timansky (Timan) coast and Bolshezemelskaya (Bolshezemel) coast -- White Sea -- Murmansk coast.; Greenwich meridian.; "No. 734" -- margins Color;